The Effect of Work Duration and Spinal Trauma on Low Back Pain in the Warship Production Support Departement - Indah Ayu Sukma Ning Dewi; Winarko; Iva Rustanti Eri Wardoyo; Demes Nurmayanti (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Low back pain (LBP) is recognized as one of the prevalent occupational ailments that can significantly influence work productivity. Within the Warship Division Production Support Department of PT. PAL Indonesia, employees have reported instances of low back pain following prolonged periods of working in a seated position, slightly bent over computer screens, for approximately 8 hours daily, in a routine manner. This study aims to analyze the correlation between the duration of work and the occurrence of spinal trauma in relation to the prevalence of low back pain. Conducted in an analytic observational framework with a cross-sectional approach, this research encompasses all personnel within the Production Support Department, comprising a sample size of 39 workers. Statistical analysis of the data was conducted employing the Fisher's Exact Test. The study outcomes indicate that 71.8% of the workers experienced LBP characterized by minimal disability, whereas the remaining 28.2% reported LBP associated with moderate disability. The study also found that the majority of workers had a moderate work duration (4-5 hours/day) (35.9%), had no spinal trauma (76.9%), and complained of LBP with minimal disability (71.8%). The statistical analysis demonstrated a significant correlation between work duration (p-value = 0.028) and spinal trauma (p-value = 0.000) with the occurrence of LBP. In order to mitigate the LBP, workers are advised to attentively address the relevant risk factors present in their workplace. This proactive approach aims to minimize the incidence of LBP arising from their routine tasks.